2015
DOI: 10.1007/s10854-015-3391-7
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and nano-scale free volume properties of polyaniline/polyvinyl alcohol nanocomposites

Abstract: Polyaniline (PANI)/polyvinyl alcohol (PVA) nanocomposites has been prepared. Scanning electron microscopy, SEM of pure PVA and PANI/PVA nanocomposite films to monitor the morphology and dispersion of PANI on the surface of the PVA films. Positron annihilation lifetime measurements were carried out, in the air, at room temperature with a conventional fast-fast coincidence spectrometer. Dielectric permittivity e 0 , dielectric loss e 00 and AC conductivity r ac of PANI/PVA nanocomposites has been achieved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
5
21
0
Order By: Relevance
“…The calculated values of “ S ” are plotted as a function of O + ion implantation fluences and shown in Figure . It is clear from the figure that “ S ” values at both the energies show opposite behavior with o ‐Ps lifetime (τ 3 ) and free volume size ( V f ), and exhibit good agreement with the reported results in the literature …”
Section: Resultssupporting
confidence: 90%
“…The calculated values of “ S ” are plotted as a function of O + ion implantation fluences and shown in Figure . It is clear from the figure that “ S ” values at both the energies show opposite behavior with o ‐Ps lifetime (τ 3 ) and free volume size ( V f ), and exhibit good agreement with the reported results in the literature …”
Section: Resultssupporting
confidence: 90%
“…Saboor et al reported the increase in dielectric constant and dielectric loss around five and eight orders of magnitude at 1 kHz by the addition of 40 wt% of PANI in styrene acrylonitrile matrix. Similarly, El‐Gamal et al recently reported PVA/PANI blends in which dielectric properties are increased around two orders of magnitude with increasing concentration of PANI in the low frequency region. Whereas, graphene as a nanofiller not only offers outstanding electrical characteristics but also have exceptional mechanical properties like tensile strength ∼130 GPa and modulus ∼1 TPa .…”
Section: Introductionmentioning
confidence: 73%
“…Organic insulating polymers blends consisting PANI has been fabricated with noticeable advancement in mechanical and electrical properties, getting enormous observance from academics and industries. The electrical properties of films and pellets of PVA/PANI and PVA/PVP, respectively, have shown upgraded electrical properties of the composites like conductivity, dielectric, etc. A high throughput transaction is extended to fabricate nonwoven, breathable, and lightweight materials consisting of fine/uniform fibers making porous texture and extremely large ratio of surface area to volume .…”
Section: Introductionmentioning
confidence: 99%